Surrogate‐assisted tolerance analysis of low‐sidelobe linear arrays with microstrip corporate feeds. (19th December 2018) - Koziel, Slawomir; Ogurtsov, Stanislav
Abstract: This paper addresses the problem of fast statistical analysis of low‐sidelobe linear arrays with microstrip corporate feeds using surrogate‐assisted methods. Tolerances normally lead to a degradation of array performance with respect to circuit and radiation pattern characteristics. Tolerances may be pertinent to array elements, spacing, feed dimensions, and microstrip substrate parameters. Sidelobe level (SLL) is affected by these parameter deviations in case of low sidelobe designs. Accurate evaluation of an SLL requires full‐wave electromagnetic (EM) simulations, which can be very computationally expensive. Consequently, performing statistical analysis directly at the level of the EM model of the array is impractical. Here, we discuss techniques that permits fast tolerance analysis yet at the high‐fidelity level of EM modeling. These include various surrogate modeling and correction techniques that are used to align the fast surrogates with the respective EM models.